2020
DOI: 10.1177/0271678x19900097
|View full text |Cite
|
Sign up to set email alerts
|

Microglia alter the threshold of spreading depolarization and related potassium uptake in the mouse brain

Abstract: Selective elimination of microglia from the brain was shown to dysregulate neuronal Ca2+ signaling and to reduce the incidence of spreading depolarization (SD) during cerebral ischemia. However, the mechanisms through which microglia interfere with SD remained unexplored. Here, we identify microglia as essential modulators of the induction and evolution of SD in the physiologically intact brain in vivo. Confocal- and super-resolution microscopy revealed that a series of SDs induced rapid morphological changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…Microglia also play an important role in this process. PS-exposed neurons are recognized either via the opsonin MFG-E8 and vitronectin receptors on microglia ( 10 ) or by the opsonin Gas6 and MerTK (Mer receptor tyrosine kinase) receptors on microglia ( 8 , 9 , 55 ). It appears that inflammatory activation of microglia impairs their ability to discriminate between apoptotic and viable neurons for phagocytosis, resulting in phagoptosis during inflammation ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microglia also play an important role in this process. PS-exposed neurons are recognized either via the opsonin MFG-E8 and vitronectin receptors on microglia ( 10 ) or by the opsonin Gas6 and MerTK (Mer receptor tyrosine kinase) receptors on microglia ( 8 , 9 , 55 ). It appears that inflammatory activation of microglia impairs their ability to discriminate between apoptotic and viable neurons for phagocytosis, resulting in phagoptosis during inflammation ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the ramified and widely nonreactive microglia are not involved in K + clearance and buffering during robust neuronal activation in situ, neither directly nor indirectly by modulating astrocyte functions (Larsen, Stoica, & MacAulay, 2016; Varga et al., 2020).…”
Section: Resultsmentioning
confidence: 97%
“…In studies investigating brain pH and DC potential, CCAo was performed by a mechanical occluder, which resulted in a larger (over 40%) and more abrupt CBF reduction, unexpectedly triggering SD, a large acidic pH shift and progressive oligaemia in the absence of microglia. Interestingly, we have previously reported altered extracellular potassium homeostasis after microglia depletion in vivo , with a lower initial SD threshold in the intact brain, but impaired SD induction after repeated SDs, or during hypoperfusion due to cerebral ischemia 21, 63 . In the presented study, microglia depleted mice immediately showed a robust, 80% drop in CBF during the first CCAo, followed by sustained impairment in CBF recovery, which was also seen in the milder CCAo model upon different microglia manipulations.…”
Section: Discussionmentioning
confidence: 92%